2020
DOI: 10.1590/1516-3180.2019.0363.09122019
|View full text |Cite
|
Sign up to set email alerts
|

Classification of plastic surgery malpractice complaints brought before the São Paulo Medical Board that were treated as professional-misconduct cases: a cross-sectional study

Abstract: BACKGROUND: Nowadays, there is an ethical and moral necessity to establish rules that govern professional attitudes and conduct. In the medical field, these rules are multifaceted, given the health consequences inherent to medical procedures. Ethics is an even more delicate subject when it comes to plastic surgery, since one of the aims of this particular medical specialty is esthetic improvement of the body. OBJECTIVE: To survey and classify São Paulo State Medical Board investigations of plastic-surgery comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This result is consistent with published data. 12 The existence of complaints of negligence, medical malpractice or recklessness makes it clear that most mistakes or misconducts that occur in the practice of plastic surgery are due to physicians' omissions or passiveness in relation to patients who should be receiving more attention and care. This is corroborated by the rate of cases found in physicians' favor on account of a lack of evidence to back up the complaints.…”
Section: Medical Ethics Code Chapters (Subject/topic)mentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with published data. 12 The existence of complaints of negligence, medical malpractice or recklessness makes it clear that most mistakes or misconducts that occur in the practice of plastic surgery are due to physicians' omissions or passiveness in relation to patients who should be receiving more attention and care. This is corroborated by the rate of cases found in physicians' favor on account of a lack of evidence to back up the complaints.…”
Section: Medical Ethics Code Chapters (Subject/topic)mentioning
confidence: 99%
“…The article governing professional responsibility is the article most often violated by doctors. 12 The Brazilian Medical Association (BMA) and regional medical boards are tasked with being notified of, investigating and ruling on all complaints filed, as well as for regulating the practice of medicine. [13][14][15] Once a professional-mis-…”
Section: Introductionmentioning
confidence: 99%
“…The article reported that the number of complaints lodged decreased over the last two years reviewed, although complaints regarding malpractice and poor doctor-patient relationships increased by 10% over the same period. 1 The specialties with the greatest number of lawsuits in the United States are gynecology/ obstetrics, general surgery and internal medicine. 2 The factors that may explain the increasing numbers of lawsuits include the population's greater knowledge about their rights and the influence of the media.…”
mentioning
confidence: 99%